2021
DOI: 10.1038/s41598-021-97950-9
|View full text |Cite
|
Sign up to set email alerts
|

A potential probiotic Leuconostoc mesenteroides TBE-8 for honey bee

Abstract: An isolated bacterium TBE-8, was identified as Leuconostoc mesenteroides according to the sequences of 16S rDNA and the 16S–23S rDNA intergenic spacer region. The probiotic properties of the L. mesenteroides TBE-8 strain were characterized and revealed that TBE-8 could utilize various carbohydrates, exhibited high tolerance to sucrose’s osmotic pressure and acidic conditions, and could mitigate the impact of the bee pathogen Paenibacillus larvae. In addition, we found that the TBE-8 broth increased the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…The notified probiotic species in Korea, Lactobacillus helveticus and Lactobacillus plantarum , were detected in makgeolli samples in the present study. In addition, some strains of Enterococcus casseliflavus, Tetragenococcus halophilus, Lactobacillus delbrueckii, Lactobacillus paraplantarum, Lactobacillus zeae, Pediococcus acidilactici, Leuconostoc mesenteroides, Weissella hellenica, Weissella paramesenteroides , and Lactococcus garvieae , which were detected in this study, have been reported to possess probiotic potential ( Ayyash et al, 2020 , Barigela and Bhukya, 2021 , Huang et al, 2021 , Inayah et al, 2022 , Kim et al, 2022 , Pabari et al, 2020 , Panthee et al, 2019 , Safari et al, 2016 , Son et al, 2018 ). These species collectively accounted for 4.65% of the relative abundance of the makgeolli microbiome, and a total cell number of 7.15 log CFU per bottle of makgeolli.…”
Section: Discussionmentioning
confidence: 55%
“…The notified probiotic species in Korea, Lactobacillus helveticus and Lactobacillus plantarum , were detected in makgeolli samples in the present study. In addition, some strains of Enterococcus casseliflavus, Tetragenococcus halophilus, Lactobacillus delbrueckii, Lactobacillus paraplantarum, Lactobacillus zeae, Pediococcus acidilactici, Leuconostoc mesenteroides, Weissella hellenica, Weissella paramesenteroides , and Lactococcus garvieae , which were detected in this study, have been reported to possess probiotic potential ( Ayyash et al, 2020 , Barigela and Bhukya, 2021 , Huang et al, 2021 , Inayah et al, 2022 , Kim et al, 2022 , Pabari et al, 2020 , Panthee et al, 2019 , Safari et al, 2016 , Son et al, 2018 ). These species collectively accounted for 4.65% of the relative abundance of the makgeolli microbiome, and a total cell number of 7.15 log CFU per bottle of makgeolli.…”
Section: Discussionmentioning
confidence: 55%
“…However, our strains L. citreum KCC-57 and L. citreum KCC-58 survived significantly in lower pH (pH 2.5) without nutrition (acidic pH in PBS) compared to previously reported Leuconostoc spp. [ 41 , 42 ]. Furthermore, the resistant capacity of L. citreum KCC-57 and L. citreum KCC-58 was found to be higher in duodenal and intestinal juices compared to gastric juice.…”
Section: Discussionmentioning
confidence: 99%
“…The exposure of honey bee larvae to LAB strains from the genus Lactobacillus spurred the immune response in larvae as evidenced by the up-regulated transcriptional expression of AMPs components, abaecin ( Evans and Lopez 2004 ) and Apidaecin 1 ( Janashia and Alaux 2016 ). The administration of Leuconostoc mesenteroides TBE-8 (Lactobacillales, Lactobacillaceae) (isolated from the hindgut of bumble bee B. eximius ) to honey bees significantly increased the transcriptional expression of nutrition-related genes (major royal jelly protein 1 in the head and vitellogenin in the abdomen) and AMPs genes (hymenoptaecin and apidaecin in the abdomen) ( Huang et al 2021 ). All the above mentioned modes of actions LAB exert on honey bees are summarized in Fig.…”
Section: Beneficial Bacteria Exhibiting Probiotic Potential In Afb Co...mentioning
confidence: 99%